PEMBELAJARAN INKUIRI MATERI OPERASI HITUNG PADA SISWA SEKOLAH DASAR - Judius Gawe (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2023)
Mathematical modelling has become one of the important competencies in the process of learning mathematics. Therefore, teachers must be able to choose strategies, methods, and learning models that can make students able to improve learning outcomes. One approach that can empower students' cognitive abilities and inquiry skills is learning using inquiry learning. The purpose of this study was to find out the learning outcomes of elementary school students by applying the inquiry learning method to the material for arithmetic operations on integers. The subjects in this study were 21 grade VI students at Nuabosi Elementary School, consisting of 10 girls and 11 boys. The type of research used in this research is classroom action research (CAR). The process of implementing this classroom action research was designed using the Kemiss & MC model. Taggart whose device consists of 4 (four) components, namely planning, action, observation and reflection. Observation data analysis techniques and student learning outcomes tests use quantitative constructs which are translated into qualitative data through interval patterns. In cycle I it increased to 47.61% and in cycle II it increased again to 100% so there was an increase of 52.39%. The measurement of the increase in learning outcomes is based on the KKM that has been determined, which is equal to 45 and classical completeness> 75%. Improved learning outcomes do not only occur in cognitive aspects but also in affective and psychomotor aspects.